2002
DOI: 10.1103/physrevd.65.104011
|View full text |Cite
|
Sign up to set email alerts
|

Maximum bounds on the surface redshift of anisotropic stars

Abstract: It is shown that for realistic anisotropic star models the surface redshift can not exceed the values 3.842 or 5.211 when the tangential pressure satisfies the strong or the dominant energy condition respectively. Both values are higher than 2, the bound in the perfect fluid case. 04.20.Cv

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
421
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(479 citation statements)
references
References 22 publications
40
421
3
1
Order By: Relevance
“…(vii) There are many other solutions of charged matter in various situations which have been discovered throughout the years. Many of them are interesting and would deserve a review, but there are too many to be quoted here, see [50] for a very partial list. (viii) Charged gravitating solutions have been also used to study Abraham type models for the electron, with and without Poincaré stresses see, e.g, [51,52,53], and also [3] and [17].…”
Section: Further Connectionsmentioning
confidence: 99%
“…(vii) There are many other solutions of charged matter in various situations which have been discovered throughout the years. Many of them are interesting and would deserve a review, but there are too many to be quoted here, see [50] for a very partial list. (viii) Charged gravitating solutions have been also used to study Abraham type models for the electron, with and without Poincaré stresses see, e.g, [51,52,53], and also [3] and [17].…”
Section: Further Connectionsmentioning
confidence: 99%
“…It is for this reason that many investigators use a variety of techniques to attain exact solutions. A comprehensive list of Einstein-Maxwell solutions, satisfying a variety of criteria for physical admissability, is provided by Ivanov [1]. The exact solutions may be used to study the physical features of charged spheroidal stars as demonstrated by Komathiraj and Maharaj [2], Sharma et al [3], Patel and Koppar [4], Patel et al [5], Tikekar and Singh [6] and Gupta and Kumar [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bhar [12,13] studied a new model of an anisotropic superdense star which admits conformal motions in the presence of a quintessence field which is characterized by a parameter w q with −1 < w q < −1/3. Charged anisotropic matter with linear equation of state [14,15] and a self gravitating, charged and anisotropic fluid sphere [16,17] were also considered For simplicity, we consider the static, spherically symmetric configurations. The stress tensor for an anisotropic fluid compatible with the spherical symmetry is…”
Section: Introductionmentioning
confidence: 99%